Geographical variation in growth form traits in Quercus suber and its relation to population evolutionary history - Ramírez-Valiente, J a.; Alia, R; Aranda, I (Evolutionary Ecology, 2013)
Differential selection pressures caused by environmental disparities lead to populations to become differentiated as they adapt to local environments. In addition, natural selection during the species past can contribute to the observed differentiation. In this study, we examine the geographic variation in a set of four traits related to growth and plant architecture in cork oak (Quercus suber) and investigate to what extent this variation is the result of the effects of ongoing evolution in current environments and the past evolutionary history of the species. Cork oak saplings at the common garden trial exhibited differences in plant architecture associated to cpDNA lineage. Eastern lineages, exhibited the lowest apical dominance and highest branchiness, consistent with the analyses in other cork oak trials. In contrast, patterns linked to the evolutionary past were less evident in height and diameter. These results suggest that selective pressures after cpDNA divergence can have blurred patterns in some traits closely related to fitness, while conserving the past evolutionary imprints in plant architectural traits. Introgressed populations did not show significant differentiation in architecture, which suggests that allele exchanges via hybridization have had a limited effect on population differentiation in cork oak. Finally, populations within lineages also showed differences in growth and architecture. Correla- tion between population architecture and temperature patterns were observed indicating that environmental factors such as climate also could result crucial in the evolution of plant architecture of cork oak within lineages
Keywords: Evolutionary history; Growth adaptation; plant architecture; Population ecology

Elevated atmospheric CO2 does not modify osmotic adjustment to light and drought in the Mediterranean oak" Quercus suber L." - Aranda, I; Simón, J Puértolas (Investigación agraria. Sistemas y recursos forestales, 2008)
The current ongoing increase in the atmospheric CO2 concentration is an unquestionable fact. Thus, plants are bound to live in a more enriched CO2 world in a not far-off future. In this new framework, regeneration of forest tree species may be modified as a consequence of the change in the current patterns of seedling response to other environmental resources, such as water or light. We studied the impact of an elevated CO2 concentration on the interaction of drought and light upon the water relations of cork oak (Quercus suber L.) seedlings. In a complete factorial design of contrasting light (HL vs LL), water (WW vs S) and CO2 levels (800 ppm vs 370 ppm), we analysed the influence of each factor and its interaction in the modification of different leaf water parameters in potted seedlings after a 6 months experimental period. These parameters were derived from the construction, with leaf materials, of the P-V curves: osmotic potential at full turgor (Ψπ100), osmotic potential at zero turgor (Ψπ0), modulus of elasticity at full turgor (εmax), and the ratio dry/turgor weight (DW/TW). Doubling of the CO2 levels over the current concentration (380 ppm) did not change any of the studied leaf water parameters, while light and water availabilities had a significant influence. This result does not exclude changes in other basic physiological parameters that could modify the pattern of cork oak regeneration responding to a CO2 enriched atmosphere in the future, and under climatic conditions different to the current ones
Keywords: CO2 enrichment; Cork oak; PV curves; shade; Water availability

Variación en la actividad del fotosistema ii de plantas de alcornoque (Quercus suber L.) SOMETIDAS A ESTRÉS HÍDRICO MODERADO Y BAJO DISTINTOS NIVELES DE RADIACIÓN - Jiménez, M D; Pardos, M; Aranda, I; Puértolas, J; Pardos, J A (IV Congreso Forestal Español, 2005)
Se estudió el efecto conjunto de la luz y la disponibilidad hídrica sobre la actividad del fotosistema II (PSII) en plantas de alcornoque (Quercus suber L.) cultivadas en vivero. Se consideraron cuatro niveles de luz (66-70% , 44-50%, 13.5-16% y 5-6%, con respecto a pleno sol) y dos de riego. La mitad de las plantas se regaron a capacidad de campo dos veces por semana (R+: 25-35% de humedad en el sustrato, medido con TDR) y la otra mitad se sometió a dos ciclos de sequía de 51 y 38 días, respectivamente (R-: hasta alcanzar una humedad en el sustrato del 7-10%). Las mediciones se realizaron al amanecer, mediodía y tarde, en cuatro fechas en hojas adaptadas a la oscuridad, empleándose un fluorómetro. Para todos los tratamientos, Fv/Fm presentó los valores más altos al amanecer, disminuyó al mediodía, y experimentó una ligera recuperación por la tarde en los tratamientos de máximo sombreo para la medición del 23 de Julio. Fv/Fm decreció a lo largo del ensayo (al mediodía y por la tarde) hasta alcanzar un mínimo tras finalizar el primer ciclo de sequía.. El riego afectó positivamente la relación Fv/Fm al amanecer solamente en la última medición del primer ciclo. Asimismo se detectó un efecto positivo en los niveles de luz intermedios (13.5% y 16%). Al mediodía y por la tarde, la eficiencia fotoquímica del PSII fue mayor con niveles de luz inferiores al 16%. La eficiciencia cuántica del fotosistema II mostró dos repuestas a las altas radiaciones una caída diaria al mediodía, como un mecanismo de fotoproctección en las horas de mayor radiación y una disminución a lo largo del tiempo que duró el ensayo. El tratamiento de riego no provocó cambios en la eficiencia cuántica del PSII, salvo en una fecha, coincidiendo con la máxima demanda evaporativa. Los tratamientos mayores de luz (>44%) provocaron una pérdida de la eficiencia cuántica del PSII.
Keywords: eficiencia fotoquímica máxima del PSII (Fv/Fm); fluorescencia máxima; fluorescencia variable

Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L; Aranda, I; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential